1990
DOI: 10.1302/0301-620x.72b6.2246287
|View full text |Cite
|
Sign up to set email alerts
|

Open reduction and fixation of proximal humeral fractures and fracture-dislocations

Abstract: Open reduction and internal fixation was employed in the freatment of 25 severely displaced fractures and fracture-dislocations of the proximal humerus. Our aims were accurate reduction and stable fixation to allow early mobilisation and to achieve full functional recovery. In 15 fractures an AO T-plate was used and in 10 a bent semitubular plate was employed as a blade plate. Excellent or satisfactory results were obtained in all six patients with two-part fractures involving the surgical neck; in four of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 0 publications
0
32
0
1
Order By: Relevance
“…The incidence of infection after rotator cuff repair ranges between 0.27% to 1.9% [3,18,27,28,37], whereas the incidence after shoulder arthroplasty ranges from 0% and 15.4% [9,11,38,41,44]. Infections after proximal humerus fractures are less common [4,29,32,40,46]. P. acnes is being recognized as a causal agent in shoulder infections with increasing frequency [3,7,14,18,33,35,37,39,45].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of infection after rotator cuff repair ranges between 0.27% to 1.9% [3,18,27,28,37], whereas the incidence after shoulder arthroplasty ranges from 0% and 15.4% [9,11,38,41,44]. Infections after proximal humerus fractures are less common [4,29,32,40,46]. P. acnes is being recognized as a causal agent in shoulder infections with increasing frequency [3,7,14,18,33,35,37,39,45].…”
Section: Introductionmentioning
confidence: 99%
“…The best results are obtained if the fracture is well reduced and planned rehabilitation program followed. 12 Szyszkowitz et al showed that fractures for open reduction and internal fixation which can be anatomically reduced. The present study was conducted to assess the results of two-part, three-part and four proximal humeral fractures treated by open reduction internal fixation by locking compression plate.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has similar results compared with other studies of surgical management of the proximal humerus. 25,[30][31][32][33][34][35][36] Proximal humerus fractures occur more commonly in the middle age group. Numerous age-related studies point toward this, and our study is consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%